Importance-performance Analysis Applied to a Laboratory Supplies and Equipment Company - Ferreira, Hélder Pires (2018)
With this study, we intended to implement a management tool to assess the degree of importance and performance of the Critical Success Factors (CSF), from the customers' perspective. For this purpose, it was used the Importance vs. Performance Matrix proposed by Martilla and James [1]. This allows through a representation on a Cartesian system identify the CSF where an organization should focus, reduce or maintain their efforts and also evaluate the CSF where the largest deviations occur between what is important to the client and which he is receiving. For data collection, it was used a questionnaire applied randomly to 225 company customers and it was assumed a sampling error of 5.8% and a significance level of 5%. The results allowed to observe that the CSF: Price Competitiveness and Strategic Management of the Company, are well positioned in the Quadrant where it is suggested that the company should continue the good work, which is a good indicator for the company.